The Influence of Environmental, Social, and Governance on the Financial Performance of Banking Companies Listed on the Indonesia Stock Exchange in the 2019-2024 Period - Theresa Echa Rianti; Fadli, Faishal (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) scores on the financial performance of banking companies measured by Return on Assets (ROA). The sample consists of banks listed on the Indonesia Stock Exchange during the 2019–2024 period. The study employs a quantitative approach using secondary data obtained from Bloomberg Terminal and annual reports. The analysis technique applied is dynamic panel regression using the System Generalized Method of Moments (System GMM), with bank size and BOPO as control variables. The results indicate that the Environmental variable has a positive and significant effect on ROA in the short term. The Governance variable has a negative and significant effect, suggesting the presence of compliance costs that may reduce short-term profitability. Meanwhile, the Social variable does not show a significant effect on ROA. Simultaneously, ESG variables influence financial performance, although the effects differ across variables. These findings imply that ESG implementation in the banking sector requires a balanced and efficient strategy to enhance sustainable performance.